Dermal Delivery of Lipid Nanoparticles: Effects on Skin and Assessment of Absorption and Safety - Pinto, Fátima (2022)
During the recent decades, dermal delivery has achieved visible popularity mainly due to the increase of chronic skin diseases and the demand for targeted delivery and patient compliance. Dermal delivery provides an attractive alternative to oral drug delivery, promoting the drug application directly at the site of action, resulting in higher localized drug concentration with reduced systemic drug exposure. Among several types of drug delivery systems used in dermal delivery are the lipid nanoparticles, which include solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs). These lipid nanocarriers have attracted great interest and have been intensively studied for their use in dermal applications. Lipid nanoparticles increase the transport of active compounds through the skin by improving drug solubilization in the formulation, drug partitioning into the skin, and fluidizing skin lipids. Moreover, these nanocarriers are composed of biologically active and biodegradable lipids that show less toxicity and offer many favorable attributes such as adhesiveness, occlusion, skin hydration, lubrication, smoothness, skin penetration enhancement, modified release, improvement of formulation appearance providing a whitening effect, and offering protection of actives against degradation. This chapter focuses on the effects of lipid nanoparticles in dermal delivery, on the types of active compounds that are used in their formulation and application, some aspects related to their possible toxicity, and a description of the most commonly used techniques for the evaluation of drug absorption on the skin.